Russian Intelligentsia in Search of an Identity : Between Dostoevsky's Oppositions and Tolstoy's Holism - Klimova, Svetlana (Value Inquiry Book Series, 2021)
Russian Intelligentsia in Search of an Identity considers the problem of the Russian intelligentsia's self-identification in its historic-philosophical and historic-cultural aspects. The monograph traces the rise of the intelligentsia, from the 18th century to the present day, problematizing its central ideas and themes. In this historical context, it proceeds to investigate the distinctive intellectual, spiritual and biographical opposition of Dostoevsky and Tolstoy in relation to the character and fate of the Russian intelligentsia, with its patterns of thought, ideology, fundamental values and behavioral models. Special attention is given to the binary patterns of the intelligentsia's consciousness, as opposed to dialogical and holistic modes of apprehension.